About the location of The falling soldier and other considerations - Penco Valenzuela, Fernando (Revista General de Información y Documentación, 2021)
In July 2020, the Forum for Historical and Democratic Memory of Espejo Comandante Pérez Salas, through the Córdoba Provincial Council, commissioned us to carry out a research project on the The falling soldier, the most reproduced image of the Spanish civil war and the birth of modern photojournalism. The main objective of the study was none other than to revise and update the most accepted hypotheses to date, which focused on Espejo (Córdoba). The most relevant results of the work, which were included in a Preliminary Report which we present here, touched on two aspects of the iconic photo: the definitive location of this and the photographic series, some 40 snapshots according to the ICP (International Center of Photography), and the identification of one of the people who appeared in the photos taken by Robert Capa and Gerda Taro, that afternoon at the beginning of September 1936. In addition, the work made it possible to locate two photos, attributed to Robert Capa, which the ICP assigned to the Córdoba front and which were taken in Castro del Río, eight kilometers east of Espejo. In one of them, historical deputies of the Spanish left could be identified: the importance of both images, which evoked the typical farewell photo, lay in the fact that they were taken shortly before The falling soldier.
Keywords: The falling soldier; ICP; Robert Capa; Gerda Taro; photojournalism; Cordoba front; Espejo; Spanish civil war; Rafael Medina